The impact of critical events of the 1980s on core functions for a selected group of local health departments. - Miller, C A (1993)
Directors of 14 public health departments were surveyed for their perceptions on the impact of 20 critical events of the 1980s on public health performance. The departments were selected in 1979 from among those that were highly regarded by public health experts for exemplary performance, especially with regard to personal health services. The departments were the subjects of intensive case studies in 1979, 1983, and again in 1992. The public health functions that were most benefited in the 1980s were assessment and policy development. The assurance function was equivocally affected. Greatest positive impact was exerted by the acquired immunodeficiency syndrome-human immunodeficiency virus epidemic, by increase in fee income, and by the Institute of Medicine report, "The Future of Public Health." Negative influences, especially on the assurance function were exerted by loss of Federal grants, demographic changes, substance abuse, and economic downturn. Other critical events had equivocal or idiosyncratic effects. Analysis of public health practice according to the functions of assessment, policy development, and assurance appears to have utility for purposes of evaluation and planning.